2002
DOI: 10.1212/wnl.58.2.314
|View full text |Cite
|
Sign up to set email alerts
|

An open-label trial of combination therapy with interferon β-1a and oral methotrexate in MS

Abstract: An open-label study was performed to evaluate the safety and efficacy of combination therapy with weekly oral methotrexate (20 mg) and interferon beta-1a (IFN beta-1a) in 15 patients with MS who had experienced exacerbations while receiving IFN beta monotherapy. Nausea was the only major side effect. A 44% reduction in the number of gadolinium-enhanced lesions seen on MRI scan was observed during combination therapy (p = 0.02). There was a trend toward fewer exacerbations. This combination therapy appears to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 10 publications
(14 reference statements)
0
36
0
2
Order By: Relevance
“…Immunosuppressor drugs (cyclophosphamide, and AZA) combined with plasma exchange failed in secondary progressive MS [7, 8]. Experimentation with the use of immunosuppressor drugs (cyclophosphamide [9], methotrexate [10], and AZA [11]) combined with IFN-β has also produced interesting findings; recently, Markovic–Plese et al [12]have reported an open-label study demonstrating a 69% reduction in the number of contrast-enhancing lesions during the combination therapy (AZA/IFN-β 1b ) in 6 patients. Controlled studies of combined AZA and IFN-β treatment are not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…Immunosuppressor drugs (cyclophosphamide, and AZA) combined with plasma exchange failed in secondary progressive MS [7, 8]. Experimentation with the use of immunosuppressor drugs (cyclophosphamide [9], methotrexate [10], and AZA [11]) combined with IFN-β has also produced interesting findings; recently, Markovic–Plese et al [12]have reported an open-label study demonstrating a 69% reduction in the number of contrast-enhancing lesions during the combination therapy (AZA/IFN-β 1b ) in 6 patients. Controlled studies of combined AZA and IFN-β treatment are not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…An open-label study has been performed to evaluate combination therapy with weekly oral methotrexate and β-interferon 1a im in patients who continued to experience relapses with β-interferon 1a im monotherapy [2]. The results were consistent with a reduction in disease activity measured on MRI and in relapse rates following addition of methotrexate.…”
Section: ■ Other Combinations With β β-Interferonsmentioning
confidence: 72%
“…In an open-label trial, Calabresi et al [70] added 20 mg of methotrexate to intramuscular IFN-beta1a for 6 months in 15 relapsing patients and found a 44 % reduction in number of gadolinium-enhancing lesions when compared with baseline scans of patients on IFN-beta-1a alone. Cohen et al [71] randomized patients with breakthrough disease on intramuscular IFN-beta-1a to combination treatment with either oral methotrexate 20 mg weekly, methylprednisolone 1 g intravenously bimonthly, or both.…”
Section: Trial Effects and Usementioning
confidence: 99%